Evaluation of circulating Dickkopf-1 as a prognostic biomarker in ovarian cancer patients - Klotz, Daniel Martin; Link, Theresa; Goeckenjan, Maren; Wimberger, Pauline; Poetsch, Anna R.; Jaschke, Nikolai; Hofbauer, Lorenz C.; Göbel, Andy; Rachner, Tilman Daniel; Kuhlmann, Jan Dominik (Clinical chemistry and laboratory medicine, 2022)
Objectives: Dickkopf-1 (DKK1) is a secreted protein, known for suppressing the differentiation and activity of bone-building osteoblasts by acting as an inhibitor of Wnt-signalling. Soluble DKK1 (sDKK1) has been proposed as prognostic biomarker for a wide range of malignancies, however, clinical relevance of sDKK1 as potential blood-based marker for ovarian cancer is unknown. Methods: sDKK1 levels were quantified in a cohort of 150 clinically documented ovarian cancer patients by a commercially available DKK1 ELISA (Biomedica, Vienna, Austria). Results: Median sDKK1 level was significantly elevated at primary diagnosis of ovarian cancer compared to healthy controls (estimated difference (ED) of 7.75 ng/mL (95% CI: 3.01-12.30 ng/mL, p=0.001)). Higher levels of sDKK1 at diagnosis indicated an increased volume of intraoperative malignant ascites (ED 7.08 pmol/L, 95% CI: 1.46-13.05, p=0.02) and predicted suboptimal debulking surgery (ED 6.88 pmol/L, 95% CI: 1.73-11.87, p=0.01). sDKK1 did not correlate with CA125 and higher sDKK1 levels predicted a higher risk of recurrence and poor survival (PFS: HR=0.507, 95% CI: 0.317-0.809; p=0.004; OS: HR=0.561, 95% CI: 0.320-0.986; p=0.044). Prognostic relevance of sDKK1 was partly sustained in wt BRCA patients (PFS: HR=0.507, 95% CI: 0.317-0.809; p=0.004). Conclusions: This is the first study demonstrating the prognostic relevance of sDKK1 in ovarian cancer patients, including those with wt BRCA 1/2 status. Our data encourage further evaluation of sDKK1 in ovarian cancer patients, possibly in terms of a therapy monitoring marker or a response predictor for sDKK1-directed targeted therapies.
Veröffentlicht von De Gruyter 25. Oktober 2021
Gesehen am 07.01.2022